“Building Bridges”: A Comparative study of “Anekantvada” of Jainism and Korzybski’s concept of transdisciplinary approach - Bhatt, Dr. Darshana (International Journal of English Literature and Social Sciences (IJELS), 2019)
The present paper is an attempt to compare the Anekantvada of Jainism and Korzybski’s concept of transdisciplinary approach and its contemporary relevance. The paper is divided into two sections. The first section analyzes the philosophy of Anekantvada and second section evaluates Korzybski ‘s views about trans disciplinary approach and make the comparative study of both the concepts.